2001
DOI: 10.1093/rheumatology/40.11.1262
|View full text |Cite
|
Sign up to set email alerts
|

Proposed preliminary core set measures for disease outcome assessment in adult and juvenile idiopathic inflammatory myopathies

Abstract: In order to develop a preliminary core set of disease outcome measures for use in clinical trials of idiopathic inflammatory myopathies (IIM), we evaluated those measures used in previous trials, assessed the validation of published instruments and discussed these at an international consensus conference. The initial proposals were further refined by a multidisciplinary group of adult and paediatric specialists experienced in IIM using the Delphi method. The proposed preliminary core set of disease activity me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
226
0
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(234 citation statements)
references
References 34 publications
0
226
0
8
Order By: Relevance
“…The 6-item core set of disease activity measures developed by the International Myositis Assessment and Clinical Studies Group (IMACS) includes physician's and patient's global assessment of disease activity rated on a 0 -10 VAS, the Manual Muscle Test (MMT), the Health Assessment Questionnaire (HAQ), serum levels of CPK (normal values Ͻ2.5 and Ͻ3.0 cat/ liter for women and men, respectively), and extraskeletal muscle activity (Myositis Intention to Treat Activity Index [MITAX]) (40). The MMT includes assessment of isometric strength in 8 muscle groups: neck flexors, gluteus medius and maximus, deltoids, biceps brachii, wrist extensors, quadriceps, and dorsiflexors of the ankle.…”
Section: Intensive Resistance Training In Pm and Dmmentioning
confidence: 99%
“…The 6-item core set of disease activity measures developed by the International Myositis Assessment and Clinical Studies Group (IMACS) includes physician's and patient's global assessment of disease activity rated on a 0 -10 VAS, the Manual Muscle Test (MMT), the Health Assessment Questionnaire (HAQ), serum levels of CPK (normal values Ͻ2.5 and Ͻ3.0 cat/ liter for women and men, respectively), and extraskeletal muscle activity (Myositis Intention to Treat Activity Index [MITAX]) (40). The MMT includes assessment of isometric strength in 8 muscle groups: neck flexors, gluteus medius and maximus, deltoids, biceps brachii, wrist extensors, quadriceps, and dorsiflexors of the ankle.…”
Section: Intensive Resistance Training In Pm and Dmmentioning
confidence: 99%
“…Skin damage caused by chronic skin lesions, such as calcinosis, is an important source of morbidity in juvenile DM, and may be associated with pain, disfigurement, and reductions in quality of life and physical function (7). For these reasons, the assessment of skin disease is part of the core sets of outcomes recommended for studies in adult and juvenile DM (8,9). Both of these proposed core sets recommend the assessment of extramuscular disease in the overall assessment of disease activity and damage.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the previously used end points have been unidimensional, focused exclusively on improvement in muscle strength in these systemic rheumatic diseases. Also, end points in IIM therapeutic trials have not been adequately validated, and investigators have used nonstandardized assessment techniques or have reported on a degree of change that does not clearly represent clinically important improvement for the measures (3,4). This use of nonstandardized outcome assessments has yielded inconclusive results, insufficient power from multiple end points, an inability to compare the results of different trials, and, overall, an absence of proven therapies for these disorders.…”
mentioning
confidence: 99%